QUESTIONNAIRE-BASED STUDY ON THE ASSESSMENT OF DOCTOR OF PHARMACY INTERNS’ KNOWLEDGE, ATTITUDE, AND PRACTICES REGARDING THE PHARMACOVIGILANCE - VENKATASUBBAIAH, MEDA; REDDY P, DWARAKANADHA; V SATYANARAYANA, SUGGALA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The present study was contemplated and done to assess the knowledge, attitude, and practices (KAP) toward adverse drug reactions (ADR) reporting and Pharmacovigilance (PV) of the Doctor of Pharmacy Pharm.D interns for the first time in South India, to get an insight into their awareness and reporting culture. Methods: A cross-sectional descriptive KAP questionnaire-based study was conducted for 6 months on Pharm.D interns. Results: A total of 603 Pharm.D interns were participated, among them 578 (95.85%) were considered for the analysis. On an average of 78.25% of the participants had a good knowledge, around 82% were aware that patients’ will be benefited from the ADR reporting. The majority of the participants had a positive attitude. Moreover, 59% had reported the ADRs through different ADR reporting procedures 52% were advised the awareness programs for improving the reporting culture, and 34% had the difficulty in deciding or diagnosing the ADR. Conclusion: The KAP of the Pharm.D interns toward the ADR reporting and PV is appreciable and may reduce the burden on the other healthcare workers and improve patient care.